Outcome of intertrochanteric fracture managed with proximal femoral nail antirotation 2 - Ghimire, Kathit Raj; Wod, Rupesh; Pokharel, Jhapindra; Adhikari, Sabina; Gurung, Subash; Baral, Yadunath N; Pant, Mahendra (Asian Journal of Medical Sciences, 2023)
Background: Intertrochanteric fracture is a common condition seen in elderly population which is managed with operative procedure in the department of orthopedics. The proximal femoral nail antirotation (PFNA) system was developed by the AO/ASIF in 2004 for this fracture that provides optimal anchoring and stability when the implant is inserted into the osteoporotic bone. The main characteristic of the implant is the use of a single blade with a large surface area and insertion of the blade compacts the cancellous bone. Aims and Objectives: The aim of the study was to study the functional outcome of intertrochanteric fracture managed with PFNA2. Materials and Methods: The prospective and observational study was conducted in patients diagnosed with intertrochanteric fracture admitted in orthopedic ward, Western Regional Hospital, Pokhara. Pre- and post-operative fracture alignment, Harris hip score (HHS), post-operative complications were taken into account. Results: Out of 55 cases taken into study, 36 (65.45%) were male and 19 (34.55%) were female. Maximum number of patients allocated in our study falls in 71–80 years group (29%) with least number in age group of 90 years or more (1.9%). Right-sided intertrochanteric fracture were 27 (49%) and left side involved were 28 (51%). Twenty-eight (51%) falls in Type II and 27 (49%) falls in Type III Boyd and Griffin intertrochanteric fractures. There was a marked improvement in fracture alignment after the operation with various parameters taken into consideration. Pre-operative HHS was 5.52±5.38 (Poor) and immediately after the procedure, it was 30.41±3.04 (Poor), 89.86±3.59 (Good) at 6 months, and 95.56±1.257 (Excellent) at 12 months. One case had blade cut out at immediate post-operative period, eight cases had surgical site infection, and five cases had GT fracture. Conclusion: This study showed that PFNA2 is an effective operative procedure in management of intertrochanteric fractures by achieving better fixation through bone impaction especially in osteoporotic bone.